2016
DOI: 10.4329/wjr.v8.i3.240
|View full text |Cite
|
Sign up to set email alerts
|

What can imaging tell us about cognitive impairment and dementia?

Abstract: Dementia is a contemporary global health issue with far reaching consequences, not only for affected individuals and their families, but for national and global socioeconomic conditions. The hallmark feature of dementia is that of irreversible cognitive decline, usually affecting memory, and impaired activities of daily living. Advances in healthcare worldwide have facilitated longer life spans, increasing the risks of developing cognitive decline and dementia in late life. Dementia remains a clinical diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 110 publications
0
20
0
1
Order By: Relevance
“…Although earlier studies in primate models suggest the possibility of separating simian immunodeficiency viruses (SIV)/AIDS from SIV encephalitis by identifying novel metabolites using MRS scanning, its clinical application in human patients has not been tested [17]. However, recent advances in in vivo molecular and structural brain imaging techniques for patients with dementia, or dementia-associated diseases like Alzheimer’s disease (AD) or Parkinson’s disease (PD), offer a great opportunity to design precise therapeutic strategies to combat the disease from its early onset [18]. …”
Section: Hiv-associated Neuropathological Complicationsmentioning
confidence: 99%
“…Although earlier studies in primate models suggest the possibility of separating simian immunodeficiency viruses (SIV)/AIDS from SIV encephalitis by identifying novel metabolites using MRS scanning, its clinical application in human patients has not been tested [17]. However, recent advances in in vivo molecular and structural brain imaging techniques for patients with dementia, or dementia-associated diseases like Alzheimer’s disease (AD) or Parkinson’s disease (PD), offer a great opportunity to design precise therapeutic strategies to combat the disease from its early onset [18]. …”
Section: Hiv-associated Neuropathological Complicationsmentioning
confidence: 99%
“…As these studies provide insight in early changes of the diseases, selective PETstudies might be useful to detect preclinical stages in which therapeutic efforts might be promising. Multimodal imaging including advanced techniques for morphological and molecular imaging are important for research in dementias, but are also more and more introduced into clinical application [43][44][45].…”
Section: Resultsmentioning
confidence: 99%
“…Although conventional MRI sequences are not successful in cortical lesions demonstration, and despite the advances in new MR techniques such as magnetic resonance spectroscopy (MRS) and diffusion tensor imaging (DTI), still conventional MRI protocols playing an important role in early diagnosis of MS or CIS (suggestive of MS) [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…The disease affects the calloso-septal interface, periventricular white matter, cerebellum, and brain stem [3,4]. Several studies revealed that most MS lesion load histologically are on the cerebral cortex specifically the gray matter and white mater interface [5], which commonly associated with cognitive disability which can be revealed by magnetic resonance imaging (MRI) [6]. It was established that lesion load measurement on brain could predict neurological disorders occurred during several years.…”
Section: Introductionmentioning
confidence: 99%